2021
DOI: 10.1002/he.20397
|View full text |Cite
|
Sign up to set email alerts
|

The rationalized myth of faculty mentoring: A critical examination of faculty experiences and institutional change

Jennifer C. Ng,
Shannon K. Portillo,
Kelli R. Thomas

Abstract: Drawing on the experience of one university seeking to improve its faculty mentoring efforts, this chapter provides a model for how organizations can facilitate the broad adoption of new mentoring practices that contextualize individual behavior in institutional norms so what results is more than a “rationalized myth.”

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In addition, faculty support should align in the areas of training, financial resources, needed equipment and software packages to meet their teaching, learning, research and assessment needs (Shelton & Pederson, 2017). Providing online faculty support is more than addressing the needs of the classroom such as learner‐centred approaches to teaching (Weimer, 2013), but also includes supporting faculty as professionals by developing communities of practice (Lave & Wenger, 1998), creating work‐life balance (Denson & Szelényi, 2022), providing non−/tenured faculty mentoring programmes (Ng et al., 2021) and addressing issues of inclusivity (Xu, 2012) for the professoriate. This echoes the work of prior research (Gregory & Salmon, 2013; Vaill & Testori, 2012) that has also identified this as a weakness in online faculty support.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, faculty support should align in the areas of training, financial resources, needed equipment and software packages to meet their teaching, learning, research and assessment needs (Shelton & Pederson, 2017). Providing online faculty support is more than addressing the needs of the classroom such as learner‐centred approaches to teaching (Weimer, 2013), but also includes supporting faculty as professionals by developing communities of practice (Lave & Wenger, 1998), creating work‐life balance (Denson & Szelényi, 2022), providing non−/tenured faculty mentoring programmes (Ng et al., 2021) and addressing issues of inclusivity (Xu, 2012) for the professoriate. This echoes the work of prior research (Gregory & Salmon, 2013; Vaill & Testori, 2012) that has also identified this as a weakness in online faculty support.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, they noted that across studies and programs, there is a confusion over definitions. Mentoring is treated as synonymous with all kinds of support and coaching but at the same time, there is considerable faith and endorsement of the script found in conventional one-on-one mentoring (Meyer & Rowan, 1977) or what Ng et al (2022) call the "rationalized myth" of faculty mentoring. We show why conventional mentoring can be inadequate for the needs and experiences of under-represented mid-career faculty, drawing on feminist mentoring models that advance relationality.…”
Section: Introductionmentioning
confidence: 99%